The complete annotated Gilbert and Sullivan - Gilbert, William S. 1836-1911; Sullivan, Arthur 1842-1900 (Oxford University Press, 2016)
Ian Bradley's "Complete Annotated Gilbert and Sullivan" has established itself across the world as the authorized and definitive 'Bible' for all those interested in the Savoy operas. Originally published in two Penguin paperbacks in the 1980s, a single-volume comprehensive compendium, hailed widely as "easily the best annotated Gilbert & Sullivan available" (Gayden Wren, New York Times) was published by Oxford University Press in 1996. This brand new 20th anniversary edition includes Thespis, Gilbert and Sullivan's first collaboration which is now being increasingly performed, despite the loss of the vocal and orchestral scores. It also features a completely new introduction, reflecting on the state of Gilbert and Sullivan nearly 150 years after the pair began their legendary collaboration, and new annotations addressing recent performance history, newly discovered 'lost' songs and dialogue, and, for the first time, Gilbert and Sullivan references in contemporary popular culture. Scholars, performers, and fans are sure to rejoice in this indispensable companion to the Gilbert and Sullivan repertoire, newly updated for the present day.